Magnetic separator for removal of organic pollutants / Nur Aisyah Mohamad Azali ... [et al.] - Mohamad Azali, Nur Aisyah; Abdul Rahman, Norazila; Taib, Nurul Izza; Saleh, Rozaina; Mazlan, Mazlini (2022)
Magnetic composite of magnetite (Fe3O4) and graphitic carbon nitride (g-C3N4) was synthesized using a co-precipitation method starting from Fe2+and Fe3+ salts and g-C3N4, which was obtained by different starting nitrogen-rich organic precursors urea and melamine by thermal polymerization technique. The composites were tested for methylene blue (MB) degradation in an aqueous solution under visible light irradiation. The physicochemical properties of the composites were characterized by XRD and FTIR. The XRD pattern shows the existence of sharp peaks, indicating that all the samples are in the crystalline phase. In addition, FTIR results revealed both bonds of C=N and C-N were at the range of 1200 cm-1 to 1600 cm-1, confirming the existence of g-C3N4. The magnetic composite for S4 and S5 enables 68.9% and 90.9% degradation of MB within 5 hours, respectively. This study demonstrates that the photocatalytic methylene blue under visible light is approximately two times greater when a mixture of urea and melamine is used as the g-C3N4 precursor than urea alone. Furthermore, the composite's high saturation magnetization suggests that the photocatalyst can be easily separated from the treated solution using a magnetic field.